The Properties of Sodalite and its Petrogenesis at the Princess Quarry, Bancroft, Ontario - James, Richard Stephen (My University, 1965)
The chemical and physical properties of nine samples of sodalite have been determined along with the physical properties of an additional thirteen samples. Taken together with selected data from the literature these data indicate that: (1) the cell dimension of sodalite is constant for samples from one deposit within the limits ascribed to experimental error (± 0.0015 A° ) and the variation of a(0) for samples from other deposits is quite limited (i.e. ±0.005 A° ); (2) the specific gravity and refractive index exhibit small but measurable variations which cannot however be related to compositional variation; (3) the variation in chemical composition for sodalite indicated by analyses from the literature appears to be in error; much of the variation is attributed to zeolite impurities which were not removed from the samples before analysis; (4) probably all sodalites are represented to within 5 per cent by 6Na AlSiO(4).2NaCl with less than 0.30 weight per cent H(2)O.
A petrographic study of the sodalite deposit at the Princess Quarry, Bancroft, Ontario, indicates that this mineral has formed from the reaction of chlorine-rich solutions with nepheline. The solutions appear to be derived from granite and syenite bodies which are regionally abundant in the vicinity of the Bancroft band of nepheline syenite gneiss. Many facts suggest that the present veins in the quarry have formed by the replacement of a pre-existing nepheline pegmatite.
Keywords: sodalite; refractive index; specific gravity; cell dimension; Bancroft